Development, testing, and feasibility of a customized mobile application for obstructive sleep apnea (OSA) risk assessment: A hospital-based pilot study - Priyanka Kapoor; Aman Chowdhry; Poonam Sengar; Abhishek Mehta (Elsevier, 2022)
Introduction: Obstructive Sleep Apnea (OSA), the most prevalent form of sleep-related breathing disorder has practical and financial limitations in diagnosis by polysomnography, hence OSA risk-assessment can identify OSA-related symptoms early. Objectives: To develop a mobile application for OSA-risk assessment and tests its validity, feasibility, and application in a hospital-based pilot sample. Study design and methods: The study comprised of two parts. Part i: Development of a mobile application "OSA-Risk Assessment Tool" using automated questionnaires. Part ii: A pilot study to screen OSA-risk in 200 patients (100 adults,100 children) from the orthodontic OPD of a Govt. Dental Hospital, using the mobile application. Internal validation by manual and mobile-based methods was done on 30 random patients. Non-parametric tests assessed the statistical differences between OSA-risk and nonOSA-risk variables. Results: The prevalence of OSA-risk was 21.4% in adults and 8% in children. In adults, OSA-risk showed significantly greater neck circumference (p = 0.0001), waist circumference(p = 0.001), body mass index(p = 0.008), daytime sleepiness, headache, and mouth breathing(p = 0.0001). In children, OSA-risk is associated with a dry mouth on awakening, daytime sleepiness, and mouth breathing, and nocturnal enuresis. The low OSA-risk patients were suggested standardized preventive management counseling and orthodontic interventions while medium to high-risk underwent sleep-specialist referrals. Conclusions: This study supports the feasibility and usability of the mobile application ''OSA-risk assessment tool'' in a hospital setup. This cost-effective tool can be advocated for self-evaluation, early detection, and awareness in pandemic times. The future upgraded versions may include preventive modules and real-time coordination with the nearest sleep clinics and specialists.